Pharmacoepidemiological study of potential drug interactions in heart and neurological outpatients - Rathore, Rashmi; Jain, Neetesh Kumar; Gupta, Mahesh Kumar; Shrivastava, Gaurav (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug-drug interaction (DDI) is a potential cause of adverse drug reactions. This study estimates the rate and factors associated with potential DDI in cardiac and neurological prescriptions from the out-patient department of various hospitals. Methods: A cross-sectional study was conducted from February to April, 2014 in various outpatients department of different hospitals in Indore. Total 60 prescriptions of cardiac and 60 prescriptions of neuro patients were collected from different hospitals. All the prescriptions were analyzes by various pharmaceutical and medical books, drug interaction checker software, and journals, etc. Results: Prescriptions having moderate drug interactions are more than that of severe and minor interactions and severity of the interaction found moderate in both type of prescriptions. Among cardiac patients 75% are male and 25% are females including all age groups, and in neuro patients, 58.33% are male, and 41.66% are females including all age groups. Types of drug interaction found in prescriptions are as follow, severe interaction (13% in cardiac, 8% in neuro), and moderate interaction (45% in cardiac, 37% in neuro), minor interaction (17% in cardiac, 25% in neuro), interaction not found (25% in cardiac, 30% in neuro patients). Conclusion: The hazards of prescribing many drugs, including side-effects, DDI and difficulties of compliance have long been recognized as particular problems when prescribing. Proper emphasis should be given to drug information center and training of clinical pharmacy across the country, which can play an important role in minimizing DDIs.